Sustainability blueprint: The role of green energy quality, energy patents, and investment among the selected OECD economies - Hafiz Waqas Kamran; Muhammad Adnan Afzal (Sustainable Futures)
This study aims to explore the impact of green quality of the energy mix, energy patents, renewable investment, and income inequality in dealing with eco-sustainability while taking the sample from the OECD economies. Quarterly observations from 2009 to 2019 have been utilized by applying the novel approach, the Method of Moments Quantile Regression (MMQR). The findings reveal that the green quality of the energy mix, energy patents, and income inequality improves eco-sustainability under lower to higher-order quantiles. Besides, renewable energy investment reduces the ecological burden only under 0.30th to 0.60th quantiles.